World class : purpose, passion, and the pursuit of greatness on and off the field - Wahl, Grant (Ballantine Books, 2024)
"The definitive collection of beloved late journalist Grant Wahl's work, and a masterclass in the art of sportswriting After Grant Wahl died of an aortic aneurysm at the 2022 FIFA World Cup in Qatar, collapsing in his press seat during a quarterfinal match, tributes to Wahl poured in from around the globe. Wahl was beloved for good reason-he was kind, generous, and unflinching in the face of injustice. He was also clearly one of the best journalists covering sports of his generation. Spanning four decades of storytelling, World Class collects for the first time the finest work of Grant Wahl, from his college thesis to his twenty-five years of reporting at Sports Illustrated to his deeply personal work for Fútbol with Grant Wahl for Substack. Grant was the multi-tool modern sportswriter: clear and direct; able to write long, short, or in between; cosmopolitan; socially aware. He never talked down to the reader but at the same time refused to sell them short. He was keen to shed light and unafraid of the heat his work might generate. --